William Saroyan on Russian Literature an It’s Classics - KHANJYAN, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
William Saroyan as a reader and writer always had a particular affection for Russian classical literature, the personalities and works of Pushkin, Gogol, Tolstoy, Dostoevsky, Chekhov and others. We can see evidence of it in a number of Saroyan’s works, as well as in his notes, talks, interviews. The material of greate interest from this point of view had been generated in Armenian language (in 1975-1978). The publication of fragments from this valuable material in translation from Armenian into Russian serves a purpose to put it in the current of Russian literary criticism.